(untitled) (Mustansiria Dental Journal, 2018)
The objective of this study aimed to assess the relation between various CW CO2 laser parameters and the thickness of the surface zone in the created carieslike lesion. A total of twenty four extracted human premolar teeth were irradiated with three various power densities (63.66, 31.83, and 15.9) W/cm2. The CO2 laser system emitted laser with 10.6m in wavelength. All samples were subjected to 3.5 pH lactic acid for 21 days to form carieslike lesion. The crowns after that were sectioned into ground cross sections and the surface zone thicknesses were measured under a polarizing microscope. Continuous wave (CW) CO2 laser had a noticeable effect on the prominence of the surface zone. The mean of the surface zone thicknesses found to be directly related to the power density of CW CO2 laser.